Prevalence of hyperdontia, hypodontia, and concomitant hypo-hyperdontia - Nareh Eshgian; Tanya Al-Talib; Stanley Nelson; Neamat Hassan Abubakr (Elsevier, 2021)
Background/purpose: Anomalies in human dentition are some of the most common occurrences of congenital abnormalities. Present study aimed to determine the prevalence of hypodontia, hyperdontia and concomitant hypo-hyperdontia (CHH) among patients attending the University of Nevada, Las Vegas (UNLV) School of Dental Medicine clinics. Materials and methods: Retrospective search was conducted on patients' clinical notes in AxiUm™. Search included using keywords such as "hypodontia", "hyperdontia", "supernumerary teeth" and "congenitally missing". Panoramic radiographs were used to confirm the hyperdontia, hypodontia or CHH for patients attending the UNLV SDM clinics from 2010 to 2018. Collected data were analyzed using the chi-square test. Results: 1101 patients were populated using the keywords. From these populated patients, 186 had hyperdontia, 23 hypodontia, and 3 presented with CHH. The distribution of males and females was 54.7% and 45.3% respectively. Hispanics, African Americans, Asians, Caucasians and ethnically unspecified patients represented 43.39%, 14.25%, 3.30%, 8.02%, and 31.13%, respectively, of those patients with a dental anomaly. Hyperdontia was most common amongst Hispanic patients with 39.24%, followed by the unspecified patients at 32.8% as well as amongst males at 56.45% (P value of 0.03). Unidentifiable supplemental teeth were overall the greatest in number with the lower right premolars, tooth 44, being the most common. This was demonstrated in the Hispanic patients whereas within the African American patients a 4th molar was in excess. Conclusion: Hispanic patient population has a significant link to dental anomalies, specifically hyperdontia while the presence of the fourth molar was prominent among African American patients.